Food Safety and Inspection : An Introduction - Smith, Madeleine; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
The process of food inspection relies on an inspector's understanding of the intrinsic hazards associated with individual foods. Whereas spoilage can usually be determined through a simple organoleptic assessment, the judgment of whether a food is fit for human consumption requires an evaluation of health hazards, many of which may not be apparent through physical assessment. Instead the inspector must analyse and integrate scientific and handling information to evaluate the potential health risk. Adulteration of foods is also becoming an increasing problem, and the complexity of the food supply chain requires an understanding of risk points to allow targeted inspection and assessment. Food Safety and Inspection: An Introduction focuses on food categories and describes common hazards associated with each, using published peer-reviewed research to explain and evaluate the health risk. It is a practical textbook designed to support the role of food inspection in a modern food industry. There are seven chapters looking at specific aspects of food safety, including a chapter on fraud and adulteration.This book summarises relevant published research to provide a scientific context for specific food safety issues, and is an essential read for anyone interested in becoming a food inspector.
1 Parasites Associated with Fish. 2 Shellfish. 3 Smoked Fishery Products. 4 Outbreaks Associated with Fruit and Vegetables. 5 Mycotoxins. 6 Parasites Associated with Meat. 7 Food Fraud.
Includes bibliographical references and index.
Also available in print format.
Keywords: Food adulteration and inspection; Electronic books